Whole-exome sequencing in pediatric patients with glomerulonephritis - Peric, Marina; Brankovic, Marija; Stajic, Natasa; Putnik, Jovana; Paripovic, Aleksandra; Jankovic, Milena; Nikolic, Dejan; Milanovic, Filip; Novakovic, Ivana; Vukomanovic, Vladislav (Frontiers in Genetics, 2025)
IntroductionHigh-throughput sequencing methods revealed disease-causing and susceptibility genes underlying glomerulonephritis (GN). Genetic disorders mimicking GN may be diagnosed in this way. The aim of this study was to perform whole-exome sequencing (WES) in a cohort of sporadic pediatric patients diagnosed with primary or secondary GN.MethodThirty-one patients with GN and 50 nephrologically and immunologically healthy pediatric patients (control group - CG) were genetically analyzed. Allele frequencies were compared with the GnomAD database. WES was performed in the laboratory 3billion in South Korea.ResultsAmong 10 patients with primary GN, two patients were positive on WES (20%). One had a likely pathogenic heterozygous variant in the COL4A3 gene associated with Alport syndrome, and one had a heterozygous novel variant of uncertain significance in the CD46 gene associated with atypical hemolytic uremic syndrome (aHUS). In two of 14 patients with systemic lupus erythematosus (SLE) and GN, a heterozygous pathogenic variant (c.841_849 + 19del) in the C2 gene was detected. We found no significant variants in seven patients with Henoch–Schönlein purpura (HSP) and GN.ConclusionWES helped us detect hereditary diseases that have a clinical presentation like GN, including Alport syndrome and possible aHUS. Finding susceptibility genes in GN helped us understand disease pathophysiology.